Praktik Kerja Sama Bagi Hasil Ternak Kambing (Kambi’) Perspektif Hukum Islam (Studi Kasus Desa Tangru Kecamatan Malua Kabupaten Enrekang) - Aswanto Muhammad Takwi Hede; Azwar Azwar; Akhmad Hanafi Dain Yunta; Muhammad Hudzaifah (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, Indonesia, 2022)
This study aims to: (1) determine the practice of sharing goats (kambi') in Tangru Village, Malua District, Enrekang Regency; and (2) knowing the views of Islamic law on the practice of sharing the results of the goat (kambi') livestock. This research is a qualitative research through field research with a normative and empirical juridical approach. The results of the study show the following things. First, the practice of kambi' in Tangru Village can be briefly described as follows: (1) related to the contract, the practice of kambi' in Tangru Village is a cooperation agreement in animal husbandry, with the object of the contract, namely goats, with a profit-sharing mechanism; (2) related to rights and obligations, livestock owners and breeders are entitled to get results according to the agreement, livestock owners are obliged to hand over capital to breeders, while breeders are obliged to care for and breed goats as the object of the contract; (3) related to risk coverage, the occurrence of losses on capital will be borne by the livestock owners as long as the losses arise due to something unintentional; and (4) regarding profit sharing, the parties agree on a 50:50 distribution ratio. Second, in the view of Islamic law, the practice of the contract is permissible, as long as it is carried out in accordance with the pillars and conditions. However, there are several notes that should be noted, namely: (1) the cooperation agreement is not made in writing; (2) there is no agreement regarding the potential loss that occurs due to negligence of the breeder; (3) there are still some cooperation actors who have not determined the profit-sharing ratio at the beginning of the contract, but only stipulate it after the goat gives birth for the first time.